Plasma neurofilament light chain as a biomarker in Wilson's disease. (February 2022) - Yang, Jie; Huang, Zihuan; Yang, Huiming; Luo, Yue; You, Huajing; Chen, Dingbang; Pei, Zhong; Li, Xunhua
Abstract: Introduction: Neurofilament light chain (NfL) was recently proposed as a promising blood biomarker for nervous system diseases, including Wilson's disease (WD). In this study, we investigated plasma NfL concentrations in patients with different types of WD and their correlations with clinical manifestations and brain atrophy. Methods: Seventy-five WD cases (54 neurological type, 21 hepatic type) and 27 age-matched healthy controls were included in this study. We compared plasma NfL concentrations between the different types and correlated them with Unified Wilson's Disease Rating Scale (UWDRS) scores. Patients were allocated to stable and unstable groups according to changes in UWDRS scores and clinical assessment. We compared the differences in plasma NfL concentrations between groups. Voxel-based morphometry (VBM) and FreeSurfer software were used to analyze MRI images. We investigated the correlation between plasma NfL concentrations and volume of gray matter, white matter, and several areas of interest in the brain MRI of 24 patients. Results: Plasma NfL concentrations were significantly higher in neurological type WD than in hepatic type WD (8.16 vs. 3.19 pg/mL, p  < 0.001). Plasma NfL concentrations were positively correlated with UWDRS scores ( r  = 0.291, p  = 0.035) in patients with neurological type WD. Plasma NfL was significantly higher in unstable patients than in stable patients (10.74 vs. 7.23 pg/mL, p  = 0.004). Significant negative associations were found between plasma NfL level and the volumes of total gray matter, bilateral caudate nucleus, putamen, and nucleus accumbens. Conclusion: Plasma NfL is valuable as a biomarker for neurological damage in patients with WD. Highlights: Neurofilament light chain (NfL) level is associated with Wilson's Disease severity. Plasma NfL was higher in Wilson's disease (WD) patients with neurological disease. Plasma neurofilament light chain concentrations reflect brain atrophy in WD.